2018
DOI: 10.1186/s12936-018-2195-7
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive therapy for severe malaria: a review and critical appraisal

Abstract: BackgroundDespite recent efforts and successes in reducing the malaria burden globally, this infection still accounts for an estimated 212 million clinical cases, 2 million severe malaria cases, and approximately 429,000 deaths annually. Even with the routine use of effective anti-malarial drugs, the case fatality rate for severe malaria remains unacceptably high, with cerebral malaria being one of the most life-threatening complications. Up to one-third of cerebral malaria survivors are left with long-term co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 143 publications
0
63
0
4
Order By: Relevance
“…These approaches are challenging both in identifying who would benefit, especially early enough in the course of illness, and in how to administer in a low resource-setting, due to their cost and potential storage requirements [19]. We direct the reader to more in-depth reviews looking at cytoadherence adjunctive therapies [2,19]. Since parasite biomass is also a predictor of progression to SM [28], whole blood transfusions and automated erythrocyte exchange, to decrease parasitemia, have been used as putative adjunctive therapies, although no randomized clinical trials have confirmed their superiority over the standard of care (reviewed in [39]).…”
Section: P Falciparum and Severe Malaria: Cytoadherence And Parasitementioning
confidence: 99%
See 2 more Smart Citations
“…These approaches are challenging both in identifying who would benefit, especially early enough in the course of illness, and in how to administer in a low resource-setting, due to their cost and potential storage requirements [19]. We direct the reader to more in-depth reviews looking at cytoadherence adjunctive therapies [2,19]. Since parasite biomass is also a predictor of progression to SM [28], whole blood transfusions and automated erythrocyte exchange, to decrease parasitemia, have been used as putative adjunctive therapies, although no randomized clinical trials have confirmed their superiority over the standard of care (reviewed in [39]).…”
Section: P Falciparum and Severe Malaria: Cytoadherence And Parasitementioning
confidence: 99%
“…Since parasite biomass is also a predictor of progression to SM [28], whole blood transfusions and automated erythrocyte exchange, to decrease parasitemia, have been used as putative adjunctive therapies, although no randomized clinical trials have confirmed their superiority over the standard of care (reviewed in [39]). Additionally, due to cost and availability, these strategies are often untenable in most low-resource settings [2]. If parasite phenotypes are reproducibly found to predict progression to SM, then parasite isolate genotyping could be exploited to risk-stratify malaria patients [28].…”
Section: P Falciparum and Severe Malaria: Cytoadherence And Parasitementioning
confidence: 99%
See 1 more Smart Citation
“…Adjunctive therapy is defined as an additional treatment that modifies the pathological processes caused by malaria to improve its clinical outcomes and/or decline mortality, along with the prevention of long-term neurocognitive impairment [13]. Over the past decades, dozens of CM interventions for different pathways have been evaluated based on immunomodulation, neuroprotection, regulation of gaseous signalling molecules and improvement of endothelial dysfunction [14]. In fact, more than 17 clinical trials have so far examined 11 treatments; however, no method has been proven effective in treating CM in children [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Infants face multiple barriers to overcoming malaria infection, including suboptimal innate immune responses to natural infection and poor antimalarial treatment efficacy, which in some cases results in serious outcomes, such as severe malarial anemia (SMA) or cerebral malaria (CM). Studies have shown that SMA and CM are driven by proinflammatory cytokine secretion and immunopathology, suggesting immunomodulation as a potential avenue for adjunctive therapy to prevent severe outcomes in infants [16, 17, 18, 19]. Although SMA and CM have been a major focus of research in infants, we were interested in identifying age-specific markers of treatment response in uncomplicated malaria (UM)—an area that is arguably less well studied and yet remains critical to understanding phenotypic variation in the majority of malaria-infected and treated infants.…”
Section: Introductionmentioning
confidence: 99%